2020
DOI: 10.3390/brainsci11010006
|View full text |Cite
|
Sign up to set email alerts
|

Motor Cortical Activity during Observing a Video of Real Hand Movements versus Computer Graphic Hand Movements: An MEG Study

Abstract: Both action observation (AO) and virtual reality (VR) provide visual stimuli to trigger brain activations during the observation of actions. However, the mechanism of observing video movements performed by a person’s real hand versus that performed by a computer graphic hand remains uncertain. We aimed to investigate the differences in observing the video of real versus computer graphic hand movements on primary motor cortex (M1) activation by magnetoencephalography. Twenty healthy adults completed 3 experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Changes reported in this study for knee mobility may also be due to the ability to alter statesthesia based on illusory visual inputs [ 37 ]. On the other hand, Hsieh et al [ 38 ] found the activation of the same cortical areas after observing a movement or performing it with the hand in healthy subjects. This could cause motion visualization to activate these areas without triggering nociceptive inputs.…”
Section: Discussionmentioning
confidence: 99%
“…Changes reported in this study for knee mobility may also be due to the ability to alter statesthesia based on illusory visual inputs [ 37 ]. On the other hand, Hsieh et al [ 38 ] found the activation of the same cortical areas after observing a movement or performing it with the hand in healthy subjects. This could cause motion visualization to activate these areas without triggering nociceptive inputs.…”
Section: Discussionmentioning
confidence: 99%
“…Given the unclear mechanisms of modulation of neural activity after AOT, a number of recent publications have examined the cortical responses of healthy adults during the observation of videos with different features. [40][41][42][43][44][45][46] The EEGbased studies by Angelini et al 40 and Ikeda et al 41 compared the cortical responses obtained by watching videos in which the manipulation of different objects was recorded from different viewing angles: AOT administered by moving specific target objects (ie, blue ball, stick, or cube) causes suppression of sensorimotor µ rhythm in α and β bands. This effect is further enhanced by color saturation.…”
Section: Introductionmentioning
confidence: 99%
“…The authors found desynchronization of the β band only during the repetition of short videos with the moving hand. Recently, Hsieh et al 44 found that observing hand movements in a video performed by a real hand and by a computer graphics hand elicited comparable activations of the primary motor cortex that were significantly different from the control videos. Other studies on cerebral activity 45 showed stronger reactivity of the primary motor cortex when observing live actions compared with videos, but also greater desynchronization of the brain cortex when observing goal-directed actions compared with non-goal-directed actions.…”
Section: Introductionmentioning
confidence: 99%
“…A video is recorded from a first-person perspective in which the observer is in the middle of the action. The use of highly realistic digital avatars promotes brain activation, produced by the viewing of the subject [ 17 ]. Dai et al [ 18 ] noted how the degree of muscle activation is directly proportional to the brain activation of the primary and secondary motor areas, and associative cortex.…”
Section: Introductionmentioning
confidence: 99%